2015
DOI: 10.3111/13696998.2015.1031794
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of adding ezetimibe to atorvastatin vs switching to rosuvastatin therapy in Portugal

Abstract: From the perspective of the National Health Service, prescribing ezetimibe to high cardiovascular risk patients being treated with atorvastatin vs switching them to rosuvastatin is projected to be a cost-effective use of resources in Portugal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Moreover, Laires et al found that prescribing ezetimibe to high cardiovascular risk patients being treated with atorvastatin instead of switching them to rosuvastatin is projected to be a cost-effective use of resources [36]. It is worth mentioning that cardiovascular benefit of administration of atorvastatin/ ezetimibe is mainly attributed to atorvastatin.…”
Section: Clinical Human Studiesmentioning
confidence: 95%
“…Moreover, Laires et al found that prescribing ezetimibe to high cardiovascular risk patients being treated with atorvastatin instead of switching them to rosuvastatin is projected to be a cost-effective use of resources [36]. It is worth mentioning that cardiovascular benefit of administration of atorvastatin/ ezetimibe is mainly attributed to atorvastatin.…”
Section: Clinical Human Studiesmentioning
confidence: 95%
“…General Characteristics of the Included Studies: We retrieved and included twenty-two potentially relevant articles 20,[26][27][28][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] for systematic review, of which 21 studies were eligible for meta-analysis 20, 26-28, 44-46, 48-61 (Figure 1). One study from the UK, Ara et al 47 , was not included for meta-analysis due to incomplete data.…”
Section: Resultsmentioning
confidence: 99%
“…Our study was in line with previous studies investigated the cost-effectiveness of ezetimibe combined with statin using different models in different clinical contexts. [35][36][37][38][39][40][41][42][43] de Labry Lima et al 35 that it is cost-effective to treat patients with high cardiovascular risk with ezetimibe plus atorvastatin than switching to rosuvastatin. In particular patients with acute coronary syndrome (ACS) 37,40 or chronic kidney disease (CKD), 41 the cost-effectiveness of the combined regimen of ezetimibe and moderate-dose statins may not be promising.…”
Section: Discussionmentioning
confidence: 99%